A study on prevalence of pre-hypertension in relation to various obesity indicators in tenth standard healthy school children aged 14 to 16 years - Shaziya, Salma; M., Soumya (International Journal of Contemporary Pediatrics, 2016)
Background: This study was carried out to know the correlation and percentage prevalance of pre-hypertension among healthy 14 to 16 year 10th standard adolescent school children and its relation to obesity indicators BMI, waist circumference, waist/height ratio. Methods: A cross sectional study done in schools of Madikeri taluka. 155 healthy adolescent school children of 10th standard aged 14-16 years were examined, Height, weight, waist circumference, blood pressure were measured using standard protocols. Children were categorized according to sex, government/private school and three obesity indicators separately using Indian standard percentile charts. Percentage prevalence of pre-hypertension (BP >90th percentile) varying with all variables noted. Data obtained analysed by descriptive and analytic statistics by using R statistical software and SSPS-16. P value <0.05 considered significant. Results: Total prevalence of pre-hypertension was 16.13%, 68% boys and 32% girls. As the BMI percentile increases the percentage prevalence of pre-hypertension increases 10.8% at 50th, 25% at 50th to 23 Eq, 57.14% at 23Eq to 27Eq and 83% at >27 Eq. As per waist circumference percentage prevalence of high BP was 11.36% at <75th, 36.3% at 75th to 90th, and 50% at >95th percentile. As per waist/height ratio percentage prevalence was 11.9% at <75th, 41.66 % at 75th to 95th and 55.56% at >95th percentile. Prevalance of overweight according to BMI (>23 Eq) is 8.48%, WC (>90th p) is 7.77%, WHtR (>95th p ) is 5.81%. Correlation between all obesity indicators and pre-hypertension were highly significant (p value >0.001). Conclusions: Percentage prevalence of pre-hypertension increases as the Percentile value of all three obesity indicators increases. Correlation between pre-hypertension and all three obesity indicators was highly significant with BMI the strongest.